The talent manifesto : how disrupting people strategies maximizes business results - Heckman, RJ (Brilliance Audio, 2019)
"In a business landscape of constant change and major disruptions, one thing remains in your full control: building a quality workforce. Who you hire, how you develop them, and what you do to retain them is all up to you-and making the right calls throughout the employee lifecycle is what will make the difference in an organization's success or its failure. From a top leader at Korn Ferry, The Talent Manifesto provides a breakthrough talent strategy for today's data-driven organizations. This guide reveals the most common dysfunctions in talent management, explains how to overcome them, and delivers provocative yet proven methods for making talent management a critical element of your company's success. You'll learn how to: Rebuild your talent strategy so it drives your company's overall business performance. Generate and apply reliable data for making high-stakes people decisions. Use artificial intelligence to enhance decision making. Advise corporate leaders what they need to do (and stop doing) to be more competitive"--Container